EFL Teachers’ Perception on Students’ Learner Autonomy: Merdeka Belajar Curriculum Context - Ahmad Fahrudin, Taufik; Rochsantiningsih, Dewi; Setyaningsih, Endang (CV. Inara, 2024)
Learner autonomy plays a critical role in fostering students' accountability for their learning. Nevertheless, the teacher's contribution remains pivotal in acquainting students with autonomous learning and in advocating methods to enhance learner autonomy. The concepts addressed in the Merdeka Belajar curriculum support learner autonomy. Therefore, Researching how EFL teachers perceive and experience student autonomy in the Merdeka Belajar Curriculum is crucial. The goal of this study is to investigate how EFL teachers perceive the concept of learner autonomy and what strategies they employ to support it. This qualitative study was carried out using the Merdeka Belajar Curriculum at senior high schools in Surakarta and the surrounding areas. In this study, semi-structured interviews and questionnaires were used to gather data. Teachers addressed an argument that decisions about students’ learning should involve them. The study's findings demonstrate that instructors have a positive perspective on student autonomy. It has been demonstrated that educators provide tactics that support students' learner autonomy.